Reviewing the importance of TLR‐NLRP3‐pyroptosis pathway and mechanism of experimental NLRP3 inflammasome inhibitors. (9th December 2021) - Kinra, Manas; Nampoothiri, Madhavan; Arora, Devinder; Mudgal, Jayesh
Abstract: Cells encounter continuous challenges due to tissue insult caused by endogenous and/or exogenous stimuli. Among the mechanisms set in place to counterbalance the tissue insult, innate immunity is always at the forefront. Cells of innate immunity efficiently recognize the 'danger signals' via a specialized set of membrane‐bound receptors known as Toll‐like receptors. Once this interaction is established, toll‐like receptor passes on the responsibility to cytosolic NOD‐like receptors through a cascade of signalling pathways. Subsequently, NOD‐like receptors assemble to a specialized multiprotein intracellular complex, that is inflammasome. Inflammasome activates Caspase‐1 and Gasdermin‐D which initiate pyroptotic cell death in the affected tissue by two simultaneous mechanisms. Being a protease, caspase‐1 cleaves and activates pro‐inflammatory cytokines IL‐1β and IL‐18. On the other hand, Gasdermin‐D causes proteolytic cleavage which forms a pore in the cell membrane. This review highlights the molecular events ranging from recognition of stimuli to pyroptosis. The review is also an attempt to discuss the mechanisms of the most specific experimental NLRP3 inhibitors.